(3SaQ MceI jShY HhSJQGLs
(3ChdgG (B:s
(3bGd cd MceI gi ef Yed GdQH hgj eYg ef bOje GdOghQ s
(3BNQgG (B:s
(3hQaYJ UhJi ef GdCQV UdjJ hOYhJ CHj ef GdSeGA Ci QHi Pi GdLHQhJ hGdNdGU dG JNPdfi s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B4s
(3fSNI ecQQIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3JHUQGJ GdCUd (B:s
(3GdfSNI eHJhQI GdBNQ s
(3MGdI GdfSNI LjOI s
Keywords: (3GdOjGfGJ GdCNQis